Efficacy of farmer FIRST Programme on knowledge and adoption of rice technologies in Khordha, Odisha - Monikarani, P; Sarbani, D; Bibhuti, P M; Abhiram, D; Khitish, K S (Plant Science Today, 2025)
The present study evaluates the effectiveness of the Farmer FIRST Programme (FFP) in enhancing farmers' knowledge and adoption of rice-based technologies, with a focus on the Pratikshya rice variety, aromatic rice (Kalajeera) cultivation and fodder cultivation in Khordha district of Odisha. Unlike traditional top-down extension models, FFP introduced by the Indian Council of Agricultural Research (ICAR) in 2016 emphasizes on participatory technology development and dissemination. The objective was to assess the programme’s impact on knowledge acquisition and technology adoption by small and marginal farmers. An ex-post facto research design was employed and data were collected from 154 respondents (77 FFP beneficiaries and 77 FFP non-beneficiaries) across four adopted villages from Begunia block using a structured and pre-tested interview schedule. Statistical analyses including frequency, percentage and Z-test were conducted using SPSS. The findings revealed a significantly higher level of knowledge and adoption frequency among FFP beneficiaries compared to non-beneficiaries. About 40.25 % of beneficiaries exhibited high knowledge levels against 23.37 % among non-beneficiaries, while only 18.18 % of beneficiaries achieved high adoption scores, in contrast to none among non-beneficiaries. The programme’s interventions such as varietal substitution in rice, scientific aromatic rice (Kalajeera) production and year-round fodder cultivation were more widely adopted among the beneficiaries. The results underscore the programme’s success in enriching knowledge and fostering meaningful adoption of location-specific technologies. To ensure sustainability and wider impact, it is essential to enhance extension support, strengthen market linkages and promote capacity-building initiatives.